High Speed Two (HS2) : infrastructure design and construction. Volume 1, (ICE Publishing, 2022)
This volume contains a collection of papers submitted to HS2's Technical Papers Competition. Contributions have come from consultants, contractors, suppliers and third-party stakeholders involved in developing the planned infrastructure of the HS2 project. As part of HS2 enduring legacy, it is incumbent upon the organisation to share its experiences and best practices with the rest of the industry and to showcase the skills of the personnel involved and the successful delivery of each phase of works.